2022
DOI: 10.1001/jama.2022.7408
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Counseling Interventions to Promote a Healthy Diet and Physical Activity for Cardiovascular Disease Prevention in Adults Without Known Cardiovascular Disease Risk Factors

Abstract: IMPORTANCE Unhealthful dietary patterns, low levels of physical activity, and high sedentary time increase the risk of cardiovascular disease.OBJECTIVE To synthesize the evidence on benefits and harms of behavioral counseling interventions to promote a healthy diet and physical activity in adults without known cardiovascular disease (CVD) risk factors to inform a US Preventive Services Task Force recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 142 publications
3
61
0
2
Order By: Relevance
“…Intensity or interaction time with a clinician may range from 30 minutes to 6 hours over 6 months or longer. 1 In determining whether behavioral counseling interventions are appropriate, patients and clinicians should consider the following.…”
Section: What Additional Information Should Clinicians Know About Thi...mentioning
confidence: 99%
See 4 more Smart Citations
“…Intensity or interaction time with a clinician may range from 30 minutes to 6 hours over 6 months or longer. 1 In determining whether behavioral counseling interventions are appropriate, patients and clinicians should consider the following.…”
Section: What Additional Information Should Clinicians Know About Thi...mentioning
confidence: 99%
“…1,38 All trials reported at least 6 months of follow-up, and many (63 trials) reported 12 months or longer. 1,38 Most trials (73 trials) included men and women. 1,38 The mean age of participants ranged widely, from 18.5 to 79.5 years.…”
Section: Benefits Of Counseling To Change Behavior and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations